2019
DOI: 10.1038/s41598-019-39229-8
|View full text |Cite
|
Sign up to set email alerts
|

Recycling endosomal CD133 functions as an inhibitor of autophagy at the pericentrosomal region

Abstract: CD133 is a transmembranous protein that mainly localises to the plasma membrane in haematopoietic and neural stem cells as well as cancer stem cells. Although CD133 also localises to the cytoplasm, the mechanism of action and function of cytoplasmic CD133 currently remain unknown. We herein demonstrated that when Src family kinase activity is weak, CD133 interacts with HDAC6 and is transported to the pericentrosomal region after internalization and endosome formation via the dynein-based traffic system. Perice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…Of relevance to this observation, high intracellular expression of CD133 has been detected in U87 glioma cells [42]. Based on this, and a recent study by Izumi et al showing that small fractions of CD133 is transported out to the plasma membrane via recycling endosomes in the U87 cells [47], we suggest that this provides sufficient CD133 receptor-mediated uptake of scFvCD133/rGelonin and reduced viability following PCI of scFvCD133/rGelonin compared to PCI of rGelonin. Concerning the MDA-MB-231 cells, several reports have shown that this cell line is also CD133-positive (as in this study, mAb clone 7 was used) [48,49].…”
Section: Discussionsupporting
confidence: 70%
“…Of relevance to this observation, high intracellular expression of CD133 has been detected in U87 glioma cells [42]. Based on this, and a recent study by Izumi et al showing that small fractions of CD133 is transported out to the plasma membrane via recycling endosomes in the U87 cells [47], we suggest that this provides sufficient CD133 receptor-mediated uptake of scFvCD133/rGelonin and reduced viability following PCI of scFvCD133/rGelonin compared to PCI of rGelonin. Concerning the MDA-MB-231 cells, several reports have shown that this cell line is also CD133-positive (as in this study, mAb clone 7 was used) [48,49].…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the role of CD133 in maintaining the undifferentiated state of cancer cells has recently been reported by inhibiting autophagy. That is, when CD133 is not phosphorylated by Src, CD133 is preferentially transported to the centrosome through the intracellular transport, and trap GABARAP, resulting in autophagy inhibition (44). These findings not only facilitate understanding the functional role of CD133 itself but also suggest the CD133 and its regulatory mechanisms as attractive therapeutic targets.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, prom1 also plays a role in autophagy where a phosphorylationdependent interaction with g-aminobutyric acid receptor-associated protein (GABARAP), an initiator of autophagy, leads to the suppression of GABARAP-mediated ULK1 kinase activation and the subsequent initiation of autophagy (82,83). The prom1 phosphorylation could link ciliogenesis and autophagy (84,85), which in turn may regulate the cell proliferation versus differentiation (86).…”
Section: Discussionmentioning
confidence: 99%